2011
DOI: 10.1007/s13346-011-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a vaginal film containing dapivirine, a non-nucleoside reverse transcriptase inhibitor (NNRTI), for prevention of HIV-1 sexual transmission

Abstract: Dapivirine, a non-nucleoside reverse transcriptase inhibitor, is a potent and promising anti-HIV molecule. It is currently being investigated for use as a vaginal microbicide in two dosage forms, a semi-solid gel and a silicone elastomer ring. Quick-dissolving films are promising and attractive dosage forms that may provide an alternative platform for the vaginal delivery of microbicide drug candidates. Vaginal films may provide advantages such as discreet use, no product leakage during use, lack of requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
119
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 42 publications
3
119
0
Order By: Relevance
“…First, the film was wrapped in butter paper as one layer and above which a second layer of aluminum foil was tightly applied. Samples of the optimized films were stored at 40 C/75% RH for a period of 12 weeks (Akil et al, 2011;Farid et al, 2015). Periodically, samples were withdrawn at different predetermined time intervals (0, 1, 2, 4, 6, 9, and 12 weeks) and examined physically for any changes in color, appearance thickness, and surface pH as well as chemically for their drug content.…”
Section: Accelerated Stability Testingmentioning
confidence: 99%
“…First, the film was wrapped in butter paper as one layer and above which a second layer of aluminum foil was tightly applied. Samples of the optimized films were stored at 40 C/75% RH for a period of 12 weeks (Akil et al, 2011;Farid et al, 2015). Periodically, samples were withdrawn at different predetermined time intervals (0, 1, 2, 4, 6, 9, and 12 weeks) and examined physically for any changes in color, appearance thickness, and surface pH as well as chemically for their drug content.…”
Section: Accelerated Stability Testingmentioning
confidence: 99%
“…UC781 and d 4 -UC781 were detected with a mass spectrometer under a positive-mode MRM scan. The mass transitions (m/z) were 360 to 268.1 for UC781 and 340 to 270.4 for d 4 …”
Section: Uc781-tfv Combination Vaginal Gelmentioning
confidence: 99%
“…In preclinical evaluations of microbicide products, assessment of the ability of drugs to permeate cervicovaginal tissue provides insight into the diffusion of drug candidates into the target tissue in vivo. The abilities of several anti-HIV-1 drugs developed as microbicide products to permeate tissue were previously evaluated in the Franz cell model using human ectocervical tissue, demonstrating drug levels that would achieve protection in vitro (4,33).…”
mentioning
confidence: 99%
“…Tablets and films, while they can be used immediately before sex, often require 30 min to dissolve fully before the start of intercourse. Moreover, microbicide films reported in literature have low drug loadings (less than 1.5 wt%) (6,7), which when coupled with their small dosage size limits their application to only highly potent antiretroviral (ARV) drugs. Recently, Ball et al and Huang et al demonstrated that electrospun fibers could release a range of active ARV drugs and spermicides (8) and that such release could occur in response to stimuli, such as a semen-induced rise in pH (9).…”
mentioning
confidence: 99%